2007
DOI: 10.1016/j.margeo.2007.03.002
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution, deep tow, multichannel seismic and sidescan sonar survey of the submarine mounds and associated BSR off Nicaragua pacific margin

Abstract: Please cite this article as: Talukder, A.R., Bialas, J., Klaeschen, D., Buerk, D., Brueckmann, W., Reston, T., Breitzke, M., High-resolution, deep tow, multichannel seismic and sidescan sonar survey of the submarine mounds and associated BSR off Nicaragua pacific margin, Marine Geology (2007Geology ( ), doi: 10.1016Geology ( /j.margeo.2007 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 40 publications
1
29
0
1
Order By: Relevance
“…Even at the cold vents of northern Cascadian margin, where should have active fluid flow, the BSRs and the BHSZs are consistent (inferred from the measured heat flow and BSR heat flow) (Riedel et al, 2006). However, some disagreements between BSRs and BHSZs (or, BSR heat flow and measured heat flow) also have been discovered (e.g., Talukder et al, 2007;Shyu et al, 2006;Lucazeau et al, 2004;Vanneste et al, 2003;Grevemeyer and Villinger, 2001;Kaul et al, 2000;Xu and Ruppel, 1999;Ruppel, 1997;Townend, 1997). Shyu et al (2006) found obvious difference between BSRs and BHSZs at Southwest Taiwan Basin.…”
Section: Introductionmentioning
confidence: 92%
“…Even at the cold vents of northern Cascadian margin, where should have active fluid flow, the BSRs and the BHSZs are consistent (inferred from the measured heat flow and BSR heat flow) (Riedel et al, 2006). However, some disagreements between BSRs and BHSZs (or, BSR heat flow and measured heat flow) also have been discovered (e.g., Talukder et al, 2007;Shyu et al, 2006;Lucazeau et al, 2004;Vanneste et al, 2003;Grevemeyer and Villinger, 2001;Kaul et al, 2000;Xu and Ruppel, 1999;Ruppel, 1997;Townend, 1997). Shyu et al (2006) found obvious difference between BSRs and BHSZs at Southwest Taiwan Basin.…”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, in some cases they have been linked to both compressional and extensional settings, such as the Western Alboran Sea area (e.g., Pérez-Belzuz, Alonso & Ercilla, 1997;Sautkin et al, 2003). In addition to high overpressure in sedimentary layers due to rapid sedimentation and gas generation (e.g., Dimitrov, 2002;Talukder et al, 2007;Brown, 1990;Hovland, Hill & Stokes, 1997), tectonic processes are considered to be the main driving mechanism for the development of mud diapirism (e.g., Milkov, 2000;Talukder et al, 2007). In Colombia, mud diapirism has been reported in scarce studies (e.g., Duque-Caro, 1984;Briceño & Vernette, 1992;Ordoñez, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to understand the tectonic development of convergent margins, it is very important to understand the fluid regime and the dewatering mechanisms as well as gas hydrate formation or dissociation processes operating in the margins. Successive geophysical and geological surveys on the Costa Rica and Nicaragua margin have identified numerous submarine landslides, a large number of mound-shaped structures and extensive BSRs along the middle upper slope of much of the margin (Pecher et al 1998;Bohrmann et al 2002;Talukder et al 2007). In general, the descriptive term 'mound' is used, because it is difficult to clearly categorize these structures as mud volcanoes, mud diapirs or any other type of mud extrusion or fluid escape features Talukder et al 2007).…”
mentioning
confidence: 99%
“…Successive geophysical and geological surveys on the Costa Rica and Nicaragua margin have identified numerous submarine landslides, a large number of mound-shaped structures and extensive BSRs along the middle upper slope of much of the margin (Pecher et al 1998;Bohrmann et al 2002;Talukder et al 2007). In general, the descriptive term 'mound' is used, because it is difficult to clearly categorize these structures as mud volcanoes, mud diapirs or any other type of mud extrusion or fluid escape features Talukder et al 2007). Talukder et al (2007) suggested that in the Nicaragua margin the triggering and distribution of mud mounds and associated BSRs are controlled by faults.…”
mentioning
confidence: 99%
See 1 more Smart Citation